Appearance of differentiated cells derived from polar body nuclei in the silkworm, Bombyx mori - Sakai, Hiroki; Yokoyama, Takeshi; Abe, Hiroaki; Fujii, Tsuguru; Suzuki, Masataka G. (Frontiers in Physiology, 2013)
Abstract In Bombyx mori, polar body nuclei are observed until 9h after egg lying, however, the fate of polar body nuclei remains unclear. To examine the fate of polar body nuclei, we employed a mutation of serosal cell pigmentation, pink-eyed white egg (pe). The heterozygous pe/+pe females produced black serosal cells in white eggs, while pe/pe females did not produce black serosal cells in white eggs. These results suggest that the appearance of black serosal cells in white eggs depends on the genotype (pe/ +pe) of the mother. Because the polar body nuclei had +pe genes in the white eggs laid by a pe/ +pe female, polar body nuclei participate in development and differentiate into functional cell (serosal cells). Analyses of serosal cells pigmentation indicated that approximately 30% of the eggs contained polar-body-nucleus-derived cells. These results demonstrate that polar-body-nucleus-derived cells appeared at a high frequency under natural conditions. Approximately 80% of polar-body-nucleus-derived cells appeared near the anterior pole and the dorsal side, which is opposite to where embryogenesis occurs. The number of cells derived from the polar body nuclei was very low. Approximately 26 % of these eggs contained only one black serosal cell. PCR-based analysis revealed that the polar-body-nucleus-derived cells disappeared in late embryonic stages (stage 25). Overall, polar-body-nuclei-derived cells were unlikely to contribute to embryos.